Técnicas activas para el desarrollo de la Pre-escritura en niños de preparatoria de la Unidad Educativa Rioblanco Alto en el año lectivo 2022-2023. - Silvia Verónica, Manotoa Cevallos (2023)
The research was oriented to solve the following problem: In what way do active techniques affect the development of fine motor skills in high school children of the Rioblanco Alto Educational Unit? For its solution, the general objective of the research was proposed: Strengthen fine motor skills through the application of active techniques in high school children. The methodology that was applied in the investigative process is characterized by starting from the qualitative-quantitative approach, the applied research modality, an explanatory design and the survey techniques applied to 5 teachers and a principal and the observation where 68 children from preparatory.